Levelling Wind : Remembering Fiji - Brij V. Lal (ANU Press, 2019)
'What I have sought to do in my work is to give voiceless people a voice, place and purpose, the sense of dignity and inner strength that comes from never giving up no matter how difficult the circumstances. History belongs as much to the vanquished as to the victors.'— Brij V. Lal‘Professor Brij Lal is the finest historian of the Indian indentured experience and the Indian diaspora. His Girmitiyas is a classic.'— Emeritus Professor Clem Seecharan, London Metropolitan University‘Brij Lal is a highly respected, versatile and imaginative scholar who has made a lasting contribution to the historiography of the Pacific.'— Dr Rod Alley, Victoria University of Wellington‘Professor Brij Lal's life is a remarkable journey of a scholar and an intellectual whose writings are truly transformative; a man of moral clarity and courage who also has deep pain at being cut off from his homeland.'— Professor Michael Wesley, Dean of the College of Asia and the Pacific, The Australian National University‘Brij Lal is a singular scholar, whose work has spanned disciplines – from history, political commentary, encyclopedia, biography and'faction'. Brij is without doubt the most eminent scholar in the humanities and social sciences Fiji has ever produced. He also remains one of the most significant public intellectuals of his country, despite having been banned from entering it in 2009.'— Emeritus Professor Clive Moore, University of Queensland‘Brij Lal is an accomplished and versatile historian and true son of Fiji. Above all, there is affirmation here of the enduring worth of good literature and the value of good education that Lal received and wants others to experience. The world needs more Lals who speak out against ruling opinions and dare to stray into the pastures of independent thought.'— Professor Doug Munro, historian and biographer, Wellington, and Adjunct Professor at the University of Queensland